2015
DOI: 10.1016/j.biopsych.2014.10.018
|View full text |Cite
|
Sign up to set email alerts
|

Cortical Thickness in Individuals at High Familial Risk of Mood Disorders as They Develop Major Depressive Disorder

Abstract: Reduced right parahippocampal and fusiform gyrus thickness are familial trait markers for vulnerability to mood disorders. Increased risk for mood disorders is associated with progressive cortical thinning in the left inferior frontal and precentral gyri in subjects who remain well. In contrast, onset of depression is associated with increasing left inferior frontal and precentral thickness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
70
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(80 citation statements)
references
References 63 publications
8
70
2
Order By: Relevance
“…Few imaging studies have applied this approach to depression. A study by Papmeyer et al followed early adult offspring (mean age, 21 yrs) at high- and low-familial risk for depression, but only across a two-year period (31). Offspring at high-risk for depression had thinner right temporal cortex, regardless of whether they developed the disorder themselves.…”
Section: Discussionmentioning
confidence: 99%
“…Few imaging studies have applied this approach to depression. A study by Papmeyer et al followed early adult offspring (mean age, 21 yrs) at high- and low-familial risk for depression, but only across a two-year period (31). Offspring at high-risk for depression had thinner right temporal cortex, regardless of whether they developed the disorder themselves.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the vertex-wise SBM approach been used to characterize patterns of GM changes in Alzheimer's disease (Blanc, et al, 2015), Parkinson's disease (Biundo, et al, 2015), and Depressive disorder (Qiu, et al, 2014), while the ROI-wise SBM approach has been used to depict brain morphometry involving socioeconomic status on children's brain structures (Jednoróg, et al, 2012), childhood maltreatment on brain structures (Kelly, et al, 2013), and brain structures of individuals with high familial risk of mood disorders (Papmeyer, et al, 2015). However, as far as we know, no studies have reported radiation-induced cortical thickness abnormalities in the normal-appearing GM for NPC patients with SBM approach.…”
Section: Introductionmentioning
confidence: 99%
“…49,[52][53][54][55][56][57][58] The specific involvement of the IFG adds to a converging body of evidence from structural and functional studies of BD. [59][60][61][62][63][64] Likewise, the involvement of the insula adds to a growing number of reports of structural and functional differences in HR cohorts. 23,[65][66][67] The involvement of a left-sided network is unique to the at-risk group (relative to CNs) and is not present in the bipolar group.…”
Section: Discussionmentioning
confidence: 99%